(3MbjbJg h eTQhYjJg s - (3eMeO Jbj GdMcje(B, (3YHO GdgGOj GdSjOs ((3HjQhJ(B:s (3efThQGJ GdMdHj(B,s, 2010)
(3GdJQGVj h GdeMd aj YbO GdJCejf, JbSje GdJCejf ef MjK GdYehe h GdNUhU , ef MjK GdehVhY h ef MjK GdGNWGQGdeqDef YdjgG , ef MjK GdZQV ef GfTGFg , ef MjK bhI GdJWHjb h ef MjK GdLgI GdJj Jbhe HOhQ GdJCejf , hLhg GdGNJdGa Hjf GfhGY GdJCejf GdKdGKI (B: (3GdJHGOdj h GdJLGQj h GdGLJeGYj , YOO NUGFU YbO GdJCejf , GdQCj Gdabgj aj YbO GdJCejf GdJHGOdj h GdJYGhfj , h aj YbO GdJCejf GdJLGQj , COdI GdbGFdjf HYOe eTQhYjI YbO GdCejf h efGbTJgG , GdJcjja Gdabj dYbO GdJCejf ef NdGd JfRjdg efRdI HYV GdYbhO GdTQYjI h efGbTJg,bjGS YbO GdJCejf GdJLGQj Ydi HYV GdGfXeI h GdYbhO GdTQYjI h efGbTJg h COdI Ydi eTQhYjI YbO GdJGejf GdJLGQj , GdJcjja Gdabgj dUMI h dRhe YbO GdJGejf GdJHGOdj h GdJYGhfj h GdJLGQj(B.s
(3eQGLY U(B.603 (3; agGQS U(B.233s
Keywords: (3GdJCejf (B- (3GdHfhcs; (3GdYbhOs